(untitled) (Journal of the College of Education for Women, 2019)
Large – Almusseiyab soils survey project in mid Mesopotamian plain havebeen chosen , because of its variation in soil series and reiteration map units, tocalculate the roundness of map units and roundness sorting values, in order to usethem as a pattern of map units shapes which help in interpret the distribution andshapes of map units, which they were (18) soil series in (141) reiteration. Calculateeach map units roundness have been done and its value ranged between (0.09) to(0.51), The average of roundness ranged between (0.250) for each MM1, MW5soil series ,and (0.317) for DW45 . 99.30 % of samples were not good roundnessand with many sineuosity. The second group was a largest percentage 38.88 % withrange of angles 6 – 7. The less value of Circularity four factor was (0.11) in MM11soil series, when the high value was (0.83) in DW56. The unit MM11 wasconsidered as a key map unit that appears in the soil of Large - Almuseiyab project,which may be used to expect another map units existence in area of that project,which is considered an important in soil survey works and management of soilstheir. All soil series appeared with poor roundness sorting ranged between (2.04) inDM115 soil series to ( 8.27 ) in MM11 . There was high correlation (0.871)between roundness sorting, area and reiterations soil series. High coefficient ofvariation of roundness sorting was (0.471), then (0.449) for Circularity four factor,finally of roundness (0.343).